Stressosome-independent but RsbT-dependent environmental stress sensing in Bacillus subtilis - Rabindra Khadka; Brannon Maravich; Natalie Demarest; Mitchell Hartwig; Andrew Tom; Niloy Kumar Das; Matthew T. Cabeen (Nature Communications)
Abstract Bacillus subtilis uses cytoplasmic complexes called stressosomes to initiate the σB-mediated general stress response to environmental stress. Each stressosome comprises two types of proteins — RsbS and four paralogous RsbR proteins — that are thought to sequester the RsbT protein until stress causes RsbT release and subsequent σB activation. RsbR proteins have been assumed to sense stress, but evidence for their sensing function has been elusive, and the identity of the true sensor has remained unknown. Here, we conduct an alanine-scanning analysis of the putative sensing domain of one of the RsbR paralogs, RsbRA. We find that single substitutions impact but do not abolish the σB response, suggesting that RsbRA has a key role in σB response dynamics and is “tunable” and robust to substitution, but not directly supporting a sensing function. Surprisingly, deletion of the stressosome does not abolish environmental stress-inducible σB activity and instead leads to a stronger and longer-lived response than in strains with stressosomes. Finally, we show that RsbT is necessary for the stressosome-independent response and that its kinase activity is also important. RsbT thus has a previously unappreciated role in initiating stress responses and may itself be a stress sensor in the general stress response.